A configuração jurídica do registro de preços: parâmetros para uma nova conformação legislativa - Tomé, Shirley Sanchez (2010)
In the system of record prices, the Administration encourages bidding, in the form of competition or auction, in order to select products and services and their suppliers. Once the winners have been selected, the Administration will hire to the extent of their convenience, subject to the stipulations of recorded prices. This is one of the most useful and interesting alternative procurement methods made available to the government, because its characteristics and specificities provide quick service for routine purchases of standardized goods or services and to obtain economies of scale for the quantities involved. Despite the importance and the achievements in terms of economy, speed and security, the record of prices has not earned the appropriate legislative treatment. As a result, discrepancies exist about the concept, the scheme, the legal nature, principles and ways of its implementation. The object of this thesis is to investigate the legal configuration of record prices and to find parameters to get a more precise delineation of legislation so as to optimize its use by the Government